Re "Underlying genetic models of inheritance in established type 2 diabetes associations" - Hemminki, Kari; Försti, Asta; Lorenzo Bermejo, Justo (American journal of epidemiology, 2010)
Genome-wide association studies have identified a large number of disease susceptibility loci of unknown function, characterized by high allele frequencies and low relative risks. This is also the case for type 2 diabetes for which Salanti et al. (1) identified 17 replicated associations from 19 studies. The odds ratios (ORs) for risk homozygotes ranged from 1.10 to 1.61. The authors compared genetic models for genotype effects and found that for 13 loci the data fitted best to the additive model, while for the remaining loci the discrimination between the additive and other models was not clear. The authors concluded that their results may be useful for predictive modeling and for designing biologic and functional experiments.
Gesehen am 19.04.2023